COLLABORATION IN THE APPLICATION OF ARTIFICIAL INTELLIGENCE-BASED TECHNOLOGY IN HERITAGE TOURISM DESTINATIONS CASE STUDY: TAMAN SARI YOGYAKARTA - Agung Yuliyanto Nugroho; Antonius Dwi Putranto Prasetyo; Aldi Wisnumurti Sarwono (PT. Jurnal Center Indonesia Publisher, 2025)
This study explores the integration of Artificial Intelligence (AI) in the development of the heritage tourism destination Taman Sari Yogyakarta. As a cultural site with rich historical and architectural values, Taman Sari has great potential to become a leading historical tourism destination through the application of modern digital technologies. This research is highly relevant in the context of the Society 5.0 era, where digital transformation and multi-stakeholder collaboration through the pentahelix model (government, academia, business sector, community, and media) are key approaches in sustainable tourism governance. The objectives of this research are: (1) to identify the potential of AI application in enhancing the attractiveness of Taman Sari as a heritage tourism site, (2) to analyze the role of local communities in the digital transformation of the destination, and (3) to formulate a structured collaborative strategy for the development of AI based heritage destinations. The research employs a qualitative method using data collection techniques including observation, in-depth interviews, and documentation. Informants included representatives from government, local communities, academia, tourism businesses, and tourists. Thematic analysis was used to interpret the data and identify patterns and meanings related to stakeholder participation and partnership. The findings indicate that AI can serve as a tool for cultural preservation and enhancement of tourist experiences, through features such as historical chatbots and augmented reality. However, challenges remain, including limited infrastructure, low digital literacy among local communities, and weak inter-stakeholder collaboration. The study also finds that local communities have the potential to act as agents of digital literacy if actively involved in training programs and AI-based tourism management. The research concludes that developing heritage tourism destinations like Taman Sari requires strong synergy among stakeholders through the formation of inclusive digital collaboration forums. AI technology can be a valuable medium for cultural preservation when implemented in a contextual, participatory, and sustainable manner.